Interleukin-27 decreases ghrelin production through signal transducer and activator of transcription 3-mechanistic target of rapamycin signaling - Heng Zhang; Qingjie Li; Yuxin Teng; Yubi Lin; Shaojian Li; Tingfeng Qin; Linxi Chen; Jiana Huang; Hening Zhai; Quan Yu; Geyang Xu (Elsevier, 2020)
Interleukin-27 (IL-27), a heterodimeric cytokine, plays a protective role in diabetes. Ghrelin, a gastric hormone, provides a hunger signal to the central nervous system to stimulate food intake. The relationship between IL-27 and ghrelin is still unexplored. Here we investigated that signal transducer and activator of transcription 3 (STAT3)-mechanistic target of rapamycin (mTOR) signaling mediates the suppression of ghrelin induced by IL-27. Co-localization of interleukin 27 receptor subunit alpha (WSX-1) and ghrelin was observed in mouse and human gastric mucosa. Intracerebroventricular injection of IL-27 markedly suppressed ghrelin synthesis and secretion while stimulating STAT3-mTOR signaling in both C57BL/6J mice and high-fat diet-induced-obese mice. IL-27 inhibited the production of ghrelin in mHypoE-N42 cells. Inhibition of mTOR activity induced by mTOR siRNA or rapamycin blocked the suppression of ghrelin production induced by IL-27 in mHypoE-N42 cells. Stat 3 siRNA also abolished the inhibitory effect of IL-27 on ghrelin. IL-27 increased the interaction between STAT3 and mTOR in mHypoE-N42 cells. In conclusion, IL-27 suppresses ghrelin production through the STAT3-mTOR dependent mechanism.